The Code of Small-Town-Dwellers: From Early Market Towns to Modern Local Communities. Issues of Self-Awareness and Identity - Kulevičius, Salvijus (Lietuvos istorijos studijos, 2025)
This article explores the issue of the existence of self-awareness of small-town-dwellers and its content in contemporary Lithuania. Self-awareness as such of small-town residents is perceived in this article as something that is commonly observed exceptionally in residents of small towns, or what would be ‘about small towns’, i.e., this is attached to or grounded on something that is manifested exceptionally in the smaller towns. This research involves three cross-sections: memory, self-awareness, and identity mechanisms; search for exceptionality of small towns in their history; and the problem area of self-awareness of the contemporary residents of small towns. It is beyond doubt that there exists some concept of residing in a minor town which persists in family memories or communicative memory of the residents of the small(er) Lithuanian towns. However, if we discuss more pronounced manifestations of self-awareness of small towns embracing greater groups of their population, or the existence of specific memory sites, they are not so evident or easy to identify. Nevertheless, the orientation of local communities to the preservation of the liveliness of small towns than to the marks of market towns manifested in the past suggests that the very phenomenon of self-awareness of small towns is, most probably, a live tradition, for the existence of which, constituent parts or factors of memory or heritage are not necessary.